Death dealer : how cops and cadaver dogs brought a killer to justice - Flora, Kate, 1949- (Far Hills, NJ : New Horizon Press, 2014)
Death Dealer is a true crime story of committed investigators from two countries and their cooperation in the relentless pursuit of a brutal murderer. David Tanasichuk reports his wife, Maria, missing. Explaining the ten-day delay in notifying authorities, David claims that he and Maria were having marital troubles and she had decided to take a break by leaving town. Suspense builds as lie after lie unravels. David's reputation for violence and drug abuse makes investigators take his veiled threats against them seriously. Local police, frustrated by a fruitless wintertime search through miles of frozen wilderness, finally enlist the aid of Maine game wardens along with cadaver dogs and their dedicated volunteer handlers. This drama culminates in a riveting courtroom drama.
Keywords: Murder -- Canada -- New Brunswick; Murder -- New Brunswick -- Miramichi -- Case studies; Murder -- Investigation -- New Brunswick -- Miramichi -- Case studies